Genetic determinants of folate status in Central Bohemia - Veselá, K; Pavlíková, M; Janosíková, B; Andel, M; Zvárová, J; Hyánek, J; Kozich, V (Physiological research, 2005)
Although several genetic factors have been implicated as determinants of blood folate concentration in various populations, their effect on folate status in the Czech population has not yet been examined. We explored whether blood folate concentrations in healthy Czech population are associated with polymorphisms in 5,10-methylenetetrahydrofolate reductase (MTHFR), folate hydrolase 1 (FOLH1), reduced folate carrier (RFC), and folate receptor (FOLR1) genes. In a cross-sectional study of 591 control subjects we determined genotypes by PCR-RFLP or ARMS-PCR methods, and plasma and erythrocyte folates by MEIA. The effect of different genotypes on folate status was examined by non-parametric tests and by regression analysis. The prevalence of the MTHFR 677C>T, MTHFR 1298A>C, FOLH1 1561C>T, RFC 80G>A and FOLR1 480G>C variant alleles was 0.34, 0.33, 0.05, 0.44 and 0.00, respectively. Only the MTHFR 677C>T variant was significantly associated with plasma folate concentrations (median 14.7, 14.0 and 12.2 nmol/l for the CC, CT and TT genotypes, respectively). Our study showed that among the five studied allelic variants, only the 677C>T polymorphism in the MTHFR gene is a significant genetic determinant of plasma folate concentrations in Czech population.
Keywords: nádory plic; kyselina listová; Lung Neoplasms; Humans; aromatické hydroxylasy; lidé středního věku; methylentetrahydrofolátdehydrogenasa (NAD+); polymorfismus genetický; mutační analýza DNA; Female; rizikové faktory; Folic Acid; Aryl Hydrocarbon Hydroxylases; Methylenetetrahydrofolate Dehydrogenase (NAD+); lidé; Polymorphism, Genetic; DNA Mutational Analysis; ženské pohlaví; Male; Middle Aged; Genetic Predisposition to Disease; genetická predispozice k nemoci; Czech Republic; potravní doplňky; Dietary Supplements; genetické testování; Risk Assessment; Genetic Testing; Česká republika; mužské pohlaví; hodnocení rizik; Risk Factors